Peningkatan Ketahanan Pangan melalui Pengembangan Sistem Hidroponik Sederhana Mengunakan Sistem Wick di Desa Ciomas, Kuningan Jawa Barat - Arip, Asep Ginanjar; Anna Fitri Hindriana; Zaenal Abidin (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2025)
This community service activity aims to enhance the knowledge and skills of the community regarding hydroponics, particularly the wick system, as an efficient and environmentally friendly solution for urban farming. Hydroponics was introduced in general through an explanation of its concepts, types of hydroponic systems, and their benefits in addressing land and water resource limitations.In the next stage, the activity focused on practical training in applying the wick hydroponic system, which is one of the simplest and easiest techniques to implement. The community was taught how to prepare tools and materials, set up the wick system using planting media, and sustainably care for the plants. Hydroponics attracts attention and is able to motivate people to practice the steps for making wick type hydroponics The results of the activity show that participants were able to understand the basics of hydroponics theoretically while also independently applying the wick method. This system is considered very effective in supporting household-scale food needs, as it can utilize recycled materials at a low cost.Through this activity, it is expected that the community can not only improve their agricultural productivity but also support the concept of sustainable and environmentally friendly farming at the community level.